Arthroscopic treatment of femoroacetabular impingement: early outcomes - POLAT, Gökhan; DİKMEN, GÖKSEL; Erdil, Mehmet; Asik, Mehmet (My University, 2013)
Objective: The aim of the study was to assess the early outcomes of the arthroscopic treatment of femoroacetabular impingement.
Keywords: femoroacetabular impingement